Vitamin C Protects Porcine Oocytes From Microcystin-LR Toxicity During Maturation - Zhang, Xue; Zhou, Changyin; Li, Weijian; Li, Juan; Wu, Wangjun; Tao, Jingli; Liu, Honglin (Frontiers in Cell and Developmental Biology, 2020)
Microcystin-leucine arginine (MC-LR) is the most toxic cyanotoxin found in water bodies. Microcystins are produced as secondary products of cyanobacteria metabolism. They have a stable structure, and can bioaccumulate in living organisms. Humans and livestock who drink fresh water containing MC-LR can be poisoned. However, few studies have reported the effects of MC-LR exposure on livestock or human reproduction. In this study, we used porcine oocytes as a model to explore the effects of MC-LR on oocyte maturation, and studied the impact of vitamin C (VC) administration on MC-LR‐induced meiosis defects. Exposure to MC-LR significantly restricted cumulus cell expansion and decreased first polar body extrusion. Further studies showed that MC-LR exposure led to meiosis arrest by disturbing cytoskeleton dynamics with MC-LR exposed oocytes displaying aberrant spindle organization, low levels of acetylate α‐tubulin, and disturbed actin polymerization. Additionally, MC-LR exposure impaired cytoplasmic maturation by inducing mitochondria dysfunction. Moreover, MC-LR also produced abnormal epigenetic modifications, and induced high levels of oxidative stress, caused DNA damage and early apoptosis. The administration of VC provided partial protection from all of the defects observed in oocytes exposed to MC-LR. These results demonstrate that MC-LR has a toxic effect on oocyte meiosis through mitochondrial dysfunction-induced ROS, DNA damage and early apoptosis. Supplementation of VC is able to protect against MC-LR-induced oocyte damage and represents a potential therapeutic strategy to improve the quality of MC-LR-exposed oocytes.